Dilation of the Subarachnoid Spaces Surrounding the Cranial Nerves with Petrous Apex Cephaloceles in Usher Syndrome - Stark, T.A.; McKinney, A.M.; Palmer, C.S.; Maisel, R.H.; Truwit, C.L. (American Journal of Neuroradiology, 2009)
SUMMARY: Limited studies of brain MR imaging findings in Usher syndrome have reported atrophy with enlarged subarachnoid spaces. However, the specific appearance of the subarachnoid spaces surrounding the cranial nerves has not yet been described. Herein we describe the skull base MR imaging findings in an adult with Usher syndrome. Multiple cranial nerve exits were enlarged to the point of causing cephaloceles with bony remodeling. A combination of uncommon findings in this rare disorder raises the question of an etiologic association.